If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -10) = -6(x + -2) + -6 Reorder the terms: 4(-10 + x) = -6(x + -2) + -6 (-10 * 4 + x * 4) = -6(x + -2) + -6 (-40 + 4x) = -6(x + -2) + -6 Reorder the terms: -40 + 4x = -6(-2 + x) + -6 -40 + 4x = (-2 * -6 + x * -6) + -6 -40 + 4x = (12 + -6x) + -6 Reorder the terms: -40 + 4x = 12 + -6 + -6x Combine like terms: 12 + -6 = 6 -40 + 4x = 6 + -6x Solving -40 + 4x = 6 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -40 + 4x + 6x = 6 + -6x + 6x Combine like terms: 4x + 6x = 10x -40 + 10x = 6 + -6x + 6x Combine like terms: -6x + 6x = 0 -40 + 10x = 6 + 0 -40 + 10x = 6 Add '40' to each side of the equation. -40 + 40 + 10x = 6 + 40 Combine like terms: -40 + 40 = 0 0 + 10x = 6 + 40 10x = 6 + 40 Combine like terms: 6 + 40 = 46 10x = 46 Divide each side by '10'. x = 4.6 Simplifying x = 4.6
| (-2a/b^4)^2 | | .20+.35(30)=29.5 | | y=x^2+2ax+4 | | .355=(×^×)/((2.82-2×)(2.83-2×)(2.83-×) | | -46+34= | | (3/10)-3 | | 62=6x-10 | | f(3)=0/21= | | 27x^2+3x-10= | | 7x-(3x+2)=62 | | 8/5m=4/15 | | 45/?=13 | | 8x+4=13+6x | | In(x+5)+(x-5)=(4x+7) | | 8/9-1/8 | | f(7)=4/49= | | v-5=12 | | 2x-10=6x^1 | | 12x^2-43x+35= | | 3y-26=55 | | 3-19=2z+6z | | 2x-10=6x^2 | | 5x=4x-80 | | -7x-3+1=3.8 | | -107-8x=-17x+19 | | 4(a+2)=2a(a+6) | | 6x=y-8 | | 3x-4=2z+7 | | (2-3y)(5y+1)= | | X+4*3=51 | | 10-3n=55 | | -9(x+3)+5(3x-7)=5(x-6)+9 |